(2-Methoxy-1,3-phenylene)diboronic acid - Dąbrowski, Marek (International Union of Crystallography, 2008)
The molecular structure of the title compound, 2-CH(3)O—C(6)H(3)-1,3-[B(OH)(2)](2) or C(7)H(10)B(2)O(5), features two intramolecular O—H⋯O hydrogen bonds of different strengths. One of the boronic acid groups is almost coplanar with the aromatic ring, whereas the second is significantly twisted. Molecules are linked by intermolecular O—H⋯O hydrogen bonds, generating infinite chains cross-linked to form a two-dimensional sheet structure aligned parallel to the (01[Image: see text]) plane.